Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan PT. Perkebunan Nusantara XIII Pabrik Minyak Sawit Paser Belengkong - Amir Hamzah; Wahyudi Wahyudi; Eliana Eliana (Jurnal Manajerial, 2021)
Background - Humans are company assets that must be nurtured and directed in order to achieve the company's goals. Its implementation refers to company regulations that have been formulated and endorsed by company management. The disciplinary factor is one that affects human resources. Purpose - This research aims to determine and analyze Effect of Work Discipline on Employee Performance in Nusantara Plantations XIII. Palm Oil Factory Paser Belengkong, East Kalimantan. Design/ Methodology/ Approach - This type of research is quantitative research. Sample taken counted 109 respondents by using Proportionate stratified random sampling and simple random sampling. Data collection is taken by using some technique that is observation, interview and questionnaire by using Likert scale, statistical analysis using Statistical Product and Service Solutions (SPSS) version 20. Result and discussion - Based on the calculation and test results, the highest work discipline variable is the preventive discipline variable (X1) partially influencing employee performance with t count 8.720> t table 1.6595. Work discipline variable simultaneously affects employee performance with F-count 66.929> F table 2.69. The next test results based on determination coefficient obtained R2 of 0.657 or 65.7%, which means that 65.7% of the dependent variable, namely Employee Performance (Y) is influenced by independent variables consisting of Preventive Discipline (X1), Corrective Discipline (X2) and Progressive Discipline (X3), while the remaining 34.3% is influenced by other variables not included in this study. Research Implications - It is expected from the research results can benefit the company in paying attention to discipline to improve employee performance and besides that it can contribute to knowledge. Limitations – This research was only conducted at PT Perkebunan Nusantara XIII Olongpinang Palm Oil Mill, Paser Belengkong Subdistrict, East Kalimantan with part of the respondents being employees so that further research is needed to expand the population.